Cardiac safety of multidrug-resistant tuberculosis treatment: moving towards individualised monitoring - Hewison, Catherine; Guglielmetti, Lorenzo (The Lancet infectious diseases, 2021)
A heart rate-corrected QT interval (QTc) of 500 ms or more increases the risk of potentially fatal ventricular arrhythmias, including torsade de pointes.2 Despite the frequent, long-term use of QT interval-prolonging drugs, including moxifloxacin, which is used as a positive control in thorough QT studies,3 ECG monitoring became routine during multidrug or rifampicin-resistant tuberculosis treatment only after the first phase 2 trials showed QT prolongation during treatment with bedaquiline and delamanid. [...]reassuring is the fact that patients with low albumin values do not appear to have clinically-relevant increases in the risk of QT prolongation, an initial concern.9 As expected, owing to bedaquiline's long half-life, QTc interval 4 weeks after treatment stop was reduced by only 25% and 26% in bedaquiline-containing groups, compared with 56% in the delamanid group. [...]these results give us the opportunity of re-establishing the correct priorities.